Pencucian Crude Palm Oil (CPO) untuk Mitigasi Penurunan 3-MCPDE dan GE pada Pemurnian Minyak Sawit - Hidayati, Baiq Pebrianti; Andarwulan , Nuri; Faridah , Didah Nur (Jurnal Teknologi dan Industri Pangan, 2024)
Crude palm oil (CPO) purification aims to remove or degrade unwanted components such as free fatty acids (FFA), phospholipids, impurities, color pigments, metals, and odors. The CPO purification generally consists of degumming, bleaching, and deodorization process. During the stages, some undesirable compounds are formed, including 3-monochloropropane-1,2-diol ester (3-MCPDE) and glycidyl ester (GE). The main precursors responsible for formation of the two compounds are chlorides and acyl glycerol fractions, especially diacylglycerol (DAG) and this occurs high temperatures in the deodorization process. Therefore, it is necessary to reduce their precursors in order to supress the contaminants. To cope with the problem, a washing process of CPO was proposed as an extra process before a purification stage. The washing process was carried out in two ways, namely wet washing by using water, and dry washing by using bleaching earth (BE) by 2 types of commercial BE (natural and acid activated). Washing processes using wet and dry washing (natural and activated BE) showed comparable effectiveness in reducing 3-MCPDE and GE levels in refined palm oil. As a result, the process successfully reduced 3-MCPDE content to comply with a standard Commission Regulation (EU) 2020/1332, but GE content did not conform to standard.